Control of the administrative activity and effective jurisdictional protection - Ruocco, Graciela (2020)
The limited extension of this study prevents us from addressing the control of any administrative activity, which is why we will restrict the analysis to the performance of the Administration in the exercise of the sanctioning power, and in particular to the assessment of the evidence produced and the exercise of the right of defense in administrative process, in the light of the principle of effective jurisdictional protection.